Immunoreactive Trypsinogen in Infants Born to Women with Cystic Fibrosis Taking Elexacaftor-Tezacaftor-Ivacaftor - Payal Patel; Jana Yeley; Cynthia Brown; Melissa Wesson; Barbara G. Lesko; James E. Slaven; James F. Chmiel; Raksha Jain; Don B. Sanders (MDPI AG, 2023)
Most people with cystic fibrosis (CF) are diagnosed following abnormal newborn screening (NBS), which begins with measurement of immunoreactive trypsinogen (IRT) values. A case report found low concentrations of IRT in an infant with CF exposed to the CF transmembrane conductance regulator (CFTR) modulator, elexacaftor-tezacaftor-ivacaftor (ETI), in utero. However, IRT values in infants born to mothers taking ETI have not been systematically assessed. We hypothesized that ETI-exposed infants have lower IRT values than newborns with CF, CFTR-related metabolic syndrome/CF screen positive, inconclusive diagnosis (CRMS/CFSPID), or CF carriers. IRT values were collected from infants born in Indiana between 1 January 2020, and 2 June 2022, with ≥1 CFTR mutation. IRT values were compared to infants born to mothers with CF taking ETI followed at our institution. Compared to infants identified with CF (n = 51), CRMS/CFSPID (n = 21), and CF carriers (n = 489), ETI-exposed infants (n = 19) had lower IRT values (p < 0.001). Infants with normal NBS results for CF had similar median (interquartile range) IRT values, 22.5 (16.8, 30.6) ng/mL, as ETI-exposed infants, 18.9 (15.2, 26.5). IRT values from ETI-exposed infants were lower than for infants with abnormal NBS for CF. We recommend that NBS programs consider performing CFTR variant analysis for all ETI-exposed infants.